2005
DOI: 10.1093/pcp/pci026
|View full text |Cite
|
Sign up to set email alerts
|

Wall-associated Kinase WAK1 Interacts with Cell Wall Pectins in a Calcium-induced Conformation

Abstract: Wall-associated kinase 1 (WAK1) is a transmembrane protein containing a cytoplasmic Ser/Thr kinase domain and an extracellular domain in contact with the pectin fraction of the plant cell walls. In order to characterize further the interaction of WAK1 with pectin, a 564 bp DNA sequence corresponding to amino acids 67-254 of the extracellular domain of WAK1 from Arabidopsis thaliana was cloned and expressed as a soluble recombinant peptide in yeast. Using enzyme-linked immunosorbent assays (ELISA), we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
247
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(255 citation statements)
references
References 70 publications
7
247
0
1
Order By: Relevance
“…The extracellular non-EGF domain of WAK1 and WAK2 was shown to bind to pectin in vitro and this is enhanced by a calcium-induced bridging of the pectin (Decreux and Messiaen 2005;Decreux et al 2006). Also, it has been shown that the assembly and crosslinking of WAKs may begin at an early stage within a cytoplasmic compartment rather than in the cell wall itself, and is coordinated with synthesis of surface cellulose (Kohorn et al 2006b).…”
Section: Functional Studies Of Different Wak Members Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular non-EGF domain of WAK1 and WAK2 was shown to bind to pectin in vitro and this is enhanced by a calcium-induced bridging of the pectin (Decreux and Messiaen 2005;Decreux et al 2006). Also, it has been shown that the assembly and crosslinking of WAKs may begin at an early stage within a cytoplasmic compartment rather than in the cell wall itself, and is coordinated with synthesis of surface cellulose (Kohorn et al 2006b).…”
Section: Functional Studies Of Different Wak Members Inmentioning
confidence: 99%
“…These results clearly suggest that anther indehiscence, reduced pollen viability and defective pollen germination may be the main reasons of sterility in the OsiWAK1-RNAi lines. The extracellular domain of WAK1 from Arabidopsis was shown to interact with cell wall pectins in a calciuminduced conformation (Decreux and Messiaen 2005). Also, pectin methyl esterases (PMEs) act as potential key regulators of pollen tube growth by determining the rheological properties of the apical pollen tube wall (Bosch et al 2005;Jiang et al 2005).…”
Section: Knockdown Of Oswak2 Mrna In Rice Plants Effects Cell Elongationmentioning
confidence: 99%
“…Notably, application of exogenous OGs protects plants against subsequent fungal infection (26,27). OGs can bind the extracellular domain of the Arabidopsis wall-associated receptor kinase 1 (WAK1) (28)(29)(30), and construction of chimeric receptors showed that activation of WAK1 by OGs triggers downstream defense responses (31), indicating that WAK1 acts as a receptor for OGs.…”
mentioning
confidence: 99%
“…WAKs are receptor like protein kinase, which are tightly linked with cell wall (He et al 1996), and are involved in regulation of cell elongation (Lally et al 2001) and expansion (Wagner and Kohorn 2001). This regulation requires a calcium-dependent binding protein to form the signaling complex (Decreux and Messiaen 2005). In Arabidopsis, the expression of WAK1 was more often seen in vascular cells with high levels of expression in older leaves than younger ones (Wagner and Kohorn 2001).…”
Section: Discussionmentioning
confidence: 99%